PENGEMBANGAN PROGRAM BELAJAR LEMBAGA KURSUS PELATIHAN KITA CENTER KOTA PEKANBARU - Rejeki, Sri Ayu; Achmad, Said Suhil; Wilson, Wilson (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The problem in this research is how is the development of learning programs conducted by the Pekanbaru Center Kita Training Course Institute ?. This study aims to find out how the development of learning programs undertaken by the Pekanbaru Kita Center Training Course Institute. This research uses a qualitative approach with a descriptive type. The informant selection technique in this study uses a purposive sampling technique. The informants in this study are people who have the information needed in the study, because the informants are people who are more knowledgeable about the problems to be studied. Data collection techniques used were observation, interviews, and documentation, and triangulation about the development of learning programs conducted by the Pekanbaru Center Kita Training Course Institute. From the results of the research conducted, it can be concluded that: 1) Aspects of the activities carried out, namely: (a) making the transition of the design of learning programs (b) to improve organizational capacity. (c) introducing learning programs through the institution's social media accounts (d) evaluating learning programs on an ongoing basis. 2) the people involved in developing learning programs conducted by the Pekanbaru Center Kita Training Course Institute are the four Founders of the Pekanbaru Center Kita Training Course Institute. 3) the places used are: Founder room, study room, and room used in programs that take place outside the Pekanbaru Center Kita Training Course Institute. 4) Next, the time used is Monday to Saturday with the range of working hours starting at 08.00 until 21.00 WIB. 5) the process of developing the learning program of the Pekanbaru City Center Training Course Institute, which is carried out by making the transition village design learning program from the beginning to become a more interesting and more program, to improve organizational capability through training activities held for trainers of the Training Course Institute Kita Center Pekanbaru City, introducing learning programs through social media accounts institutions that are marketing the learning program and the institution itself to be better known by the public and will further support the development of learning programs, evaluating learning programs on an ongoing basis through input obtained both from within and from outside the institution. 6) the aim of developing a learning program is to continue to be able to provide the best service for learning citizens who are adjusted to their interests and needs by following the changing times so that the institution can also continue to run.Key Words: Program Development, Learning